2009
DOI: 10.1021/om900517d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Hydrogen Activation by the Frustrated Lewis Pairs of ClB(C6F5)2 and HB(C6F5)2 and Bulky Lewis Bases

Abstract: The frustrated Lewis pair (FLP) derived from ClB(C6F5)2 and the bulky Lewis bases 2,2,6,6-tetramethylpiperidine (TMP), tri-tert-butylphosphine, and tris(2,4,6-trimethylphenyl)phosphine cleaved H2 heterolytically to form the intermediate anion [HClB(C6F5)2]−, which quickly underwent hydride/chloride exchange with the remaining ClB(C6F5)2 to give the known compound [HB(C6F5)2] n (n = 1 or 2) and the anion [Cl2B(C6F5)2]− present in the products [TMPH][Cl2B(C6F5)2] (1a), [t-Bu3PH][Cl2B(C6F5)2] (2a), and [Mes3PH][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…[19] 1,2-Linked (vicinal) FLPs that do not form intramolecular dative bonds are rare, but known. [15,23] Our results indicate that dimerization by B(m-H) 2 B bridges leads to a stable species for aminoborane 1 as well, for which trans-(1) 2 was found to be the prevailing form both in the solid state and in solution. On the other hand, fairly stable fourmembered heterocycles are already observed when the steric hindrance is slightly decreased.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…[19] 1,2-Linked (vicinal) FLPs that do not form intramolecular dative bonds are rare, but known. [15,23] Our results indicate that dimerization by B(m-H) 2 B bridges leads to a stable species for aminoborane 1 as well, for which trans-(1) 2 was found to be the prevailing form both in the solid state and in solution. On the other hand, fairly stable fourmembered heterocycles are already observed when the steric hindrance is slightly decreased.…”
mentioning
confidence: 66%
“…According to the Gutmann-Beckett and Childs acidity scales, the Lewis acidity of inorganic boranes BX 3 (X = H or halogen) is comparable to that of the commonly used borane B(C 6 F 5 ) 3 . [14,15] Another critical issue in our approach is the reduced size of the BX 2 unit, which may restrict the reactivity by different quenching modes. [14,15] Another critical issue in our approach is the reduced size of the BX 2 unit, which may restrict the reactivity by different quenching modes.…”
mentioning
confidence: 99%
“…Although the Repo group [28] described the H 2 activation using amines and boranes, Erker and co-workers [29][30][31] developed the FLP catalysts using linked phosphonium borates. A number of exciting applications related to FLPs have already emerged [32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The reversibility of H 2 activation for a few P/B pairs was examined with various experiments in order to apply the reactivity of FLPs to develop new approaches to H 2 storage. 18 The FLP derived from ClB(C 6 F 5 ) 2 and the bulky Lewis bases 2,2,6,6-tetramethylpiperidine (TMP), tri-tert-butylphosphine, and tris(2,4,6-trimethylphenyl)phosphine was found to cleave H 2 heterolytically to form the intermediate anion [HClB(C 6 F 5 ) 2 ] À , which quickly underwent hydride/ chloride exchange with the remaining ClB(C 6 F 5 ) 2 to give the known compound [HB(C 6 F 5 ) 2 ] n (n = 1 or 2) with the anion [Cl 2 B(C 6 19 In continuation, para-substitution found previously for classical phosphine adducts of B(C 6 F 5 ) 3 under warming to yield the air-and moisture-stable zwitterions R 3 P-C 6 H 4 B(F)(C 6 F 5 ) 2 , was observed for smaller phosphines after the combined toluene solutions of the reagents were heated under reflux, confirming the general character of this reaction. 20 In computational studies of H 2 activation by FLPs, Pa´pai and co-workers suggested generation of a phosphine-borane ''encounter complex'', stabilized by HÁÁÁF interactions.…”
Section: Preparationmentioning
confidence: 99%
“…24 The reactions of FLPs with alkenes, aldehydes, and a variety of other small molecules, including carbon dioxide, in cooperative three-component processes, offer new strategies and perspectives for synthetic chemistry. Thus, the FLP formed by the combination of tBu 3 P and B(C 6 F 5 ) 3 reacts with 1,3-dienes to give zwitterionic 1,4-addition phosphonium borates, e.g., (19), the geometry of which appears to be dominated by the steric demands of the substrate. 25 Estimation of the ability of phosphonium borates of the form [R 3 PH][B(C 6 F 5 ) 4 ], R 2 PHC 6 F 4 BF(C 6 F 5 ) 2 and R 2 PHC 4 H 8 OB(C 6 F 5 ) 3 (R 2= Cg 2 , Mes 2 , tBu(Mes), tBu 2 ) as well as the phosphine-boranes R 2 PC 6 F 4 B(C 6 F 5 ) 2 to activate CpTiMe 2 (NPtBu 3 ) for olefin polymerization both in stoichiometric and catalytic reactions, suggest that metal-based FLPs are uniquely reactive.…”
Section: Preparationmentioning
confidence: 99%